Studi Konseptual Strategi Pengembangan Reservoir Oil Rim Menggunakan Referensi Global - Andrian Suhartanto; Nor Hidayatullah (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2020)
Various efforts have been made to increase oil reserves in the upstream oil and gas industry. One of them is by exploring the thin oil reservoir layer, also known as the reservoir oil rim. The reservoir oil rim can act as a hydrocarbon container that provides alternative reserves to be developed with outputs increasing the value of oil production. In developing a new reservoir oil rim in a field, the selection of reservoir oil rim depletion strategies needs to be supported by technical justification in the form of screening methods and appropriate strategies based on best practices and lessons learned from global reference fields that have developed reservoir oil rim. The right strategy is expected to be able to provide a production effect in the form of significant recovery factor output. It is expected that the concept of developing the reservoir oil rim can be a new innovation in the exploration of alternative oil reserves in the upstream petroleum industry.